Trauma counseling [ theories and interventions - Levers, Lisa Lopez (Springer Publishing Company, 2012)
"Trauma Counseling is a comprehensive, multidisciplinary guide to the theory and treatment of survivors of a broad spectrum of traumatic events, including interpersonal violence, hate crimes, school violence, community violence, natural disasters, and war and terrorism. It is written by a Fulbright scholar who is internationally recognized for her work with traumatized populations in Rwanda, several southern African countries, Russia, and the United States. It also includes the contributions of researchers from the United States, Australia, Africa, and Europe. The book discusses evidence-based assessment and intervention techniques and integrates the latest findings from neuropsychology and psychopharmacology. It focuses on issues of loss and grief, survivorship and disability, genocide, natural disasters, the impact of war on civilians and veterans, and the distinct effects of trauma in early childhood, childhood, and adolescence. Also addressed are ethical perspectives and methods of self-care for counselors who work with this population. The text will be of value to graduate counseling students and professional counselors as well as social workers, psychologists, psychiatric nurses, and other human service providers, who will be able to attend to trauma survivors with a depth of knowledge and confidence. The contents of Trauma Counseling not only fulfill but exceed the requirements of The Council of Accreditation and Counseling and Related Educational Program (CACREP) standards"--Provided by publisher